YOGA ASANAS PRACTICE IN IMPROVING STUDENTS’ COGNITIVE POWER AS THE IMPLEMENTATION OF CHARACTER EDUCATION - Ni Putu Eni Astuti; Putu Beny Pradnyana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to describe the shift in cognitive abilities and the reinforcement of students’ character through yoga asanas practice. This qualitative descriptive study involved students of SDN 2 Sesetan, Denpasar, Bali. Data were collected through interviews and observations, then analyzed based on students’ learning concentration and character reinforcement during yoga extracurricular activities, as well as the systematic implementation and materials of yoga asanas. The findings revealed that: (1) yoga asanas improved students’ learning concentration by 71%, (2) yoga asanas strengthened students’ character, particularly in key aspects such as independence, religiosity, and integrity, by 85%, and (3) the type of yoga taught was Hatha Yoga, with main practices including Pavanamuktasana I, Hamsa Asana, Surya Namaskara, Chandra Namaskara, and Acro Yoga. The practice followed systematic steps including prayer, asana stretching, the core asana practice, asana relaxation, pranayama, and simple meditation.